The Racławka Valley – an example of an educational geosite related to the development of a Paleozoic carbonate platform // Dolina Racławki – przykład geostanowiska edukacyjnego związanego z rozwojem paleozoicznej platformy węglanowej - Szczurek, Stanisław; Bąk, Marta; Dulemba, Paweł (Geotourism/Geoturystyka, 2020)
The location and most interesting geological features of the Upper Devonian through Lower Carboniferous limestones in the Racławka Valley were presented. The limestones outcropped almost continuously along the natural valley cutting. They comprise over 60 million years of continuous growth of the carbonate platform, which developed on the ancient terrane – the Upper Silesian Block. Geosites described herein may constitute a destination for geological trips for undergraduate students of Environmental Sciences, where they can actively discover the development of an ancient carbonate platform and accompanied post depositional structures. // W dolinie Racławki znajdują się ważne geologicznie naturalne odsłonięcia wapieni (od późnego dewonu do wczesnego karbonu). Wapienie te obejmują okres ponad 60 milionów lat ciągłej sedymentacji węglanowej, która występowała na obszarze paleozoicznego kratonu – bloku górnośląskiego. Opisane stanowiska mogą być celem wycieczek geologicznych studentów pierwszego stopnia studiów przyrodniczych, w czasie których mogą oni w aktywny sposób śledzić rozwój kopalnej platformy węglanowej i struktur postdepozycyjnych.